Adsorptive Removal of Pb(II) Ions from Aqueous Solution Using a Coir-Based Product (Puresorbe) - D. Nityanandi; C.V. Subbhuraam (Adsorption Science & Technology)
The effectiveness of Pb(II) ion removal from wastewater by adsorption methods has made this an ideal alternative to other expensive treatment options. This paper describes an investigation using a coir-based adsorbent (Puresorbe) for the removal of Pb(II) ions from aqueous solution. The adsorption of Pb(II) ions was studied varying parameters such as the agitation time, the metal ion concentration, the adsorbent dose, the temperature and the pH of the aqueous solution. The experimental isotherm data were analyzed using the Langmuir, Freundlich, Dubinin–Radushkevich (D–R) and Tempkin isotherms. For a particle size of 250–500 μm at pH 3.0, the adsorption process followed second-order kinetics. The monolayer adsorption capacity at 30°C was 55.81 mg Pb(II) ion/g Puresorbe. The thermodynamic parameters showed the endothermic nature of Pb(II) ion adsorption. Desorption studies carried out using distilled water adjusted to a pH value of 2.0–7.0 suggested that the adsorption mode could be ion exchange. As the adsorbent raw material is discarded as waste during coir processing, usage of this material is expected to be economically viable.